The Field of Strategy: In Search of a Walking Stick - Thomas, Howard (Institutional Knowledge at Singapore Management University, 2005)
The question of whether there is an academic field of strategy is important. It is the question that defines the area of strategic management and all the research and teaching that takes place under its name. In this paper we argue that there is a field of strategy, but it is still underdeveloped despite an incredible surge of research in the last twenty years. We believe that most strategy research does not really address the defining issues and that it has become less and less relevant to practising managers. There has been a drift to traditional social science approaches because of the complexity of strategic issues. This has increased confusion among practitioners and academics alike. Despite the fact that practice and theory are not well connected and that strategic management has so far failed to produce the volume of useful results expected by managers, the search for truly useful ‘walking sticks’ for strategists will succeed, thus, enabling them to combine theory with practice.